2000
DOI: 10.2337/diacare.23.7.962
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes on coronary artery disease in women and men: a meta-analysis of prospective studies.

Abstract: A meta-analysis of prospective studies O R I G I N A L A R T I C L EOBJECTIVE -Women are at a much lower risk of coronary disease mortality than men are. It is widely believed that diabetes "erases" this female advantage, increasing the risk of heart disease much more in women than in men. In reality, the extent of this increased risk is controversial, with studies showing conflicting results and wide confidence intervals. Clarification of this issue has implications for the pathogenesis of coronary disease, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
248
6
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(281 citation statements)
references
References 36 publications
21
248
6
4
Order By: Relevance
“…Future prospective studies are needed to evaluate which metabolic control surrogate (and corresponding cut-off point) should be used according to pharmacological treatment, evolution of prediabetes/ diabetes, weight control, physical activity, nutritional variables and comorbidities observed in the patients. Assessment of coronary risk by gender in each glycemic status group revealed that IFG men have a significantly higher risk than their female counterparts, similar to previous results from Modrego et al [47]; however, it should be noted that coronary risk remained similar between genders among diabetics, demonstrating the role of T2DM as a gender-independent cardiovascular risk factor [48]. Although the presence of IFG has been associated with increased cardiovascular risk through its association with comorbities such as dyslipidemia and hypertension [49], several studies have proposed possible mechanisms which chronic IFG may trigger endothelial dysfunction, or at least, play a role in atherogenesis by increasing production of reactive oxygen species [50], advanced glycation endproducts [51], and inducing low-grade inflammation [52].…”
Section: Discussionsupporting
confidence: 75%
“…Future prospective studies are needed to evaluate which metabolic control surrogate (and corresponding cut-off point) should be used according to pharmacological treatment, evolution of prediabetes/ diabetes, weight control, physical activity, nutritional variables and comorbidities observed in the patients. Assessment of coronary risk by gender in each glycemic status group revealed that IFG men have a significantly higher risk than their female counterparts, similar to previous results from Modrego et al [47]; however, it should be noted that coronary risk remained similar between genders among diabetics, demonstrating the role of T2DM as a gender-independent cardiovascular risk factor [48]. Although the presence of IFG has been associated with increased cardiovascular risk through its association with comorbities such as dyslipidemia and hypertension [49], several studies have proposed possible mechanisms which chronic IFG may trigger endothelial dysfunction, or at least, play a role in atherogenesis by increasing production of reactive oxygen species [50], advanced glycation endproducts [51], and inducing low-grade inflammation [52].…”
Section: Discussionsupporting
confidence: 75%
“…Our results show indeed a differential effect of diabetes mellitus, which was a significant risk factor for longer term mortality among females with AMI but not among males with AMI. This gender-specific effect has been described earlier (Crowley et al, 2003;Lee et al, 2000), and suggested explanations include HDL cholesterol, estrogens, coagulation, patterns of obesity, or hyperinsulinemia (Lee et al, 2000) and lower use of effective cardiac medications in female than male diabetics (Crowley et al, 2003). The discussion of these theories and others is beyond the scope of this article; suffice to say that the underlying basis for the gender differences in risk from diabetes remains, for the most part, speculative.…”
Section: Discussionmentioning
confidence: 73%
“…Second, risk factors may have differential effects for males and females. A meta-analysis showed that the impact of diabetes on CHD mortality is greater for females (Lee et al, 2000), while males show greater effects of disability, cholesterol and smoking (Janghorbani et al, 1993;Kattainen et al, 2004;Marang-van de Mheen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicated a greater relative risk of CVD with diabetes [4,14] and hyperglycaemia [7,11,15] among women than men, while the Hoorn Study reported no consistent differences [9]. Two previous meta-analyses, which included studies that did not adjust for major CVD risk factors, concluded that diabetes is a stronger risk factor for CVD mortality in women than in men [16,17]. A recent meta-analysis indicated that the excess relative risk of CVD mortality in women compared with men who had diabetes was absent after adjusting for classic CVD risk factors [18].…”
mentioning
confidence: 99%